Differences in the Patterns of In-Work Poverty in Germany and the UK - Marco Giesselmann (European Societies, 2015)
This study analyses differences in individual-level working poverty determinants between Germany and the UK. These differences are linked to institutional patterns at the country level. Here, we observe that the two countries differ especially in bargaining centralisation, employment protection legislation and family policy. At the same time, the levels of decommodification and labour market regulation are no longer core differences in the institutional settings of Germany and the UK, which is interpreted as a consequence of Germany's departure from a traditional conservative regime since the mid-1990s. Adopting economic and sociological approaches, we explain how Germany's closed employment system channels the effects of deregulation policies to the periphery of the labour market. Additionally, we argue that open employment relationships that dominate in the UK put specifically older employees at risk. Finally, we identify country-specific differences in the economic dependency of women, resulting from a stronger male breadwinner orientation of family policy in Germany. Accordingly, multivariate analyses based on harmonised versions of the British Household Panel Study (2002–2005) and the Socio-Economic Panel Study (2003–2006) reveal that entrants and re-entrants to the labour market, women and – unexpectedly – low-educated persons are particularly affected by in-work poverty in Germany; whereas older workers are more likely to face precarious economic conditions in the UK.
Additional information: This is an Accepted Manuscript of an article published by Taylor & Francis in European Societies 17 (2015), 1, p. 27-46, available online: http://www.tandfonline.com/doi/abs/10.1080/14616696.2014.968796
Keywords: 330; working poor; poverty; Germany; UK; deregulation; centralisation; family policy